TEENAGERS` PERSONALITY FEATURES IN RELATION WITH AGE, GENDER AND BODY MASS INDEX - Cristina Petrescu; Brigitha Vlaicu (European Scientific Journal, ESJ, 2014)
The aim of our performed study was to identify if the age, gender and Body Mass Index (BMI) can modify the personality profiles established by applying Freiburg Personality Inventory in a teenager’s population to a specific age group (15-18 years). As material we used a sample of 2908 teenagers, homogenous and statistical representative. The Freiburg questionnaire was administered individually and anonymously, during 30 minutes. We identified no differences in personality profiles depending on age, and depending on low and high levels of BMI. An easier increased nervousness was identified for girls, not significant statistically different in comparison with the boys. The criticism was also a little increased in girls, still included in the interval for standardized population (4 - 6). The teenagers with BMI between 17 and 25 presented an easier increased nervousness. In conclusion, we did not identified a significant statistically influence of the age, gender and BMI on the personality profiles. These results do not sustain the action of these variables as confounding factors on established profiles to a specific age group (teenage group), despite of the demonstrated action of the age and gender on certain FPI personality features separately.